Predictors Of Outcome Following Anterior Cruciate Ligament Reconstruction: A Prospective Cohort Study In Uk Sports Medicine. (2nd June 2019) - Neal, Bradley Stephen; Miller, Stuart; Small, Claire; Lack, Simon David
Abstract : Background/Aims: Following anterior cruciate ligament reconstruction, patients are reported to be at greater risk of re-rupture if they fail to meet structured discharge criteria. This prospective cohort study aimed to provide objective and subjective measures guiding safe return to play of amateur athletes following anterior cruciate ligament reconstruction. Methods: Primary anterior cruciate ligament reconstruction patients presenting to Pure Sports Medicine were invited to participate. Successful return to play was determined using the Patient-Specific Functional Scale at the primary end point (9/12 post-operative), with scores >8 indicating successful outcomes. Secondary data were collected at baseline (Knee Injury and Osteoarthritis Outcome Score, Anterior Cruciate Ligament-Quality of Life), 3/12 (Knee Injury and Osteoarthritis Outcome Score, Anterior Cruciate Ligament-Quality of Life, quadriceps and hamstrings dynamometry), 6/12 (Knee Injury and Osteoarthritis Outcome Score, Anterior Cruciate Ligament-Quality of Life, quadriceps and hamstrings dynamometry, single/triple hop) and 9/12 post-operative (Knee Injury and Osteoarthritis Outcome Score, Anterior Cruciate Ligament-Quality of Life, quadriceps and hamstrings dynamometry, single/triple hop and slalom run). Binary logistic regression was used to determine the association between secondary data and the primary outcome. Results: A total of 90 participants with anterior cruciate ligament reconstruction were recruited from March 2017 to June 2018, and 87 participants consented to baseline measures. To date, 29 participants have completed full data collection, with 12 participants determined to have a successful outcome. A lower hamstrings:quadriceps ratio in the contralateral limb at 3/12 post-operative (odds ratio: 0.005, 95% confidence interval: 0.001–0.89, P=0.045) and a higher Anterior Cruciate Ligament-Quality of Life score at 6/12 post-operative (odds ratio: 1.1, 95% confidence interval: 0.02–1.20, P=0.012) are associated with positive 9/12 post-operative outcomes. Conclusions: Preliminary data analysis indicates that both hamstrings:quadriceps ratio function and participant psychology are associated with positive outcomes post-anterior cruciate ligament reconstruction.